Aspectos astronómicos de la arquitectura maya en la costa nororiental de la península de Yucatán - Hobel, Martin (Prostor, kraj, čas, 2016)
An archaeoastronomical study recently accomplished in the Maya area revealed that the architecture on the northeast coast of the Yucatán peninsula is characterized by some peculiar orientation trends, which we have not been able to explain in a satisfactory manner. In order to acquire additional information, in November 2015 we measured the orientations of 34 structures at 21 archaeological sites. The book presents the results of this work, as well as some analyses based on all the available data from the northeast coast. Their distribution shows that the percentage of orientations related to the Sun is notably lower than in other parts of the Maya Lowlands.